Fake engagement, Nashville style - Bennett, Jules (Harlequin desire, 2021)
"Cassandra Taylor's ex-fiancé owes her -- big time. Luke Sutherland shattered her dreams of happily-ever-after, and now she wants his help landing the wedding planning event of the year: his brother's celebrity nuptials. But Luke demands her help in return -- pretend to be in love with him so he's no longer Country Beat's most eligible bachelor. As their fake engagment rekindles real passion, will Cassie get her own fairy-tale wedding... or only more heartbreak?" --